2021
DOI: 10.4102/sajbm.v52i1.2395
|View full text |Cite
|
Sign up to set email alerts
|

African organisational coaching practice: Exploring approaches used, and the factors influencing coaches’ fees

Abstract: Purpose: More context-specific research regarding the praxis of organisational coaching was needed for increased understanding of this emerging profession. Whilst progress was being made internationally, African coaching practice research was sparse, leading to potentially false assumptions about local praxis based on international trends. The aim of this research was to gain a context-specific perspective on the coaching approaches used by organisational coaches in Africa and the factors that influence the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…However, not everyone has access to a coach, especially in less affluent societies. In Africa, for example, the average cost of an organisational coach is approximately 100 USD per session, which puts it out of reach of many [ 52 ]. The problem is not only cost.…”
Section: Potential Benefits and Ethical Challenges In Ai Coachingmentioning
confidence: 99%
“…However, not everyone has access to a coach, especially in less affluent societies. In Africa, for example, the average cost of an organisational coach is approximately 100 USD per session, which puts it out of reach of many [ 52 ]. The problem is not only cost.…”
Section: Potential Benefits and Ethical Challenges In Ai Coachingmentioning
confidence: 99%
“…Although the term praxis can become clouded by philosophical positions on the importance of theory, practically this paper concurs with Penney and Warelow ( 1999 , p. 259) that in coaching “praxis can (and should) become a practical process that can be applied to one's own practice with the intent of changing, reshaping and discovering new meanings or drawing out the meanings which were always there.” The eclectic origins of coaching naturally leads coaches to consciously and sub‐ consciously adapting their praxis based on what the situation and client requires. Terblanche et al ( 2021 ), for example, found that coaches use simplistic coaching practices (goal‐focused) for less complex coaching topics (career progression), but employed advanced coaching practices (cognitive behavioral) for more complex topics (diversity issues). A recent coaching praxis survey also found that most coaches adapt their praxis based on the situational requirements (Sherpa Coaching, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The eclectic origins of coaching naturally leads coaches to consciously and sub-consciously adapting their praxis based on what the situation and client requires. Terblanche et al (2021), for example, found that coaches use simplistic coaching practices (goal-focused) for less complex coaching topics (career progression), but employed advanced coaching practices (cognitive behavioral) for more complex topics (diversity issues). A recent coaching praxis survey also found that most coaches adapt their praxis based on the situational requirements (Sherpa Coaching, 2020).…”
Section: Introductionmentioning
confidence: 99%